Report on the progress of selection of TiLV disease resistance - Izadi, Fariba (WorldFish, 2024)
Infectious disease is one of the main issues threatening the success and sustainability of Nile tilapia production. The Tilapia Lake Virus (TiLV) has emerged as a major threat to Nile tilapia. Combining the new trait data with genomic tools identified several significant QTLs throughout the Nile tilapia genome. In addition, the first tests of genomic selection have been performed in the GIFT breeding program, which promises to increase the response to selection while also reducing the inbreeding rate compared with a pedigree-based approach.